1998
DOI: 10.1071/ah980133
|View full text |Cite
|
Sign up to set email alerts
|

Is there equity in emergency medical care? Waiting times and walk-outs in South Western Sydney hospital emergency departments

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 15 publications
3
28
2
Order By: Relevance
“…Sex and postcode did not predict waiting times. Hence we found no evidence that the patient characteristics identified in the Australian study 9 were important predictors of prolonged waiting times in the UK. The most important factors affecting waiting time were related to time of presentation.…”
Section: Discussioncontrasting
confidence: 58%
“…Sex and postcode did not predict waiting times. Hence we found no evidence that the patient characteristics identified in the Australian study 9 were important predictors of prolonged waiting times in the UK. The most important factors affecting waiting time were related to time of presentation.…”
Section: Discussioncontrasting
confidence: 58%
“…Studies in other countries including Canada, UK and Australia showed WBS rates from 4.5% to 8.2% 5–7. The WBS patients have lower acuity, are younger and more often male than other patients in the ED 2–4 8. The WBS rates have been found to be related to ED overcrowding2 9 and to the overall length of time patients stay in the ED before leaving 2 3.…”
Section: Introductionmentioning
confidence: 99%
“…3 6-8 16 Most of these previous studies were limited to examining the association of sociodemographic characteristics and urgency of presentation with the walkout of patients from emergency departments. [6][7][8] However, none of this research had followed up patients after they left emergency departments without treatment. This paper explores the characteristics of patients who left an emergency department without being seen by a doctor at a tertiary principal referral hospital and follows-up the walkout patients after 7 days by telephone, to identify the reason for walkout, and health services utilisation after the emergency department visit.…”
mentioning
confidence: 99%